Eutectic salt-assisted planetary centrifugal deagglomeration for single-crystalline cathode synthesis - Yoon, Moonsu; Dong, Yanhao; Huang, Yimeng; Wang, Baoming; Kim, Junghwa; Park, Jin-Sung; Hwang, Jaeseong; Park, Jaehyun; Kang, Seok Ju; Cho, Jaephil; Li, Ju (Nature energy, 2023)
Single-crystalline layered cathodes are often desirable for advanced lithium-ion batteries. However, constrained by the accessible temperature range to prevent lithium evaporation, lattice defects and particle agglomerations, the production of single-crystalline cathodes with high phase purity, good electrochemical performance and scalability remains challenging. Here we invent a new mechanochemical activation process that offers a general solution to the conundrum of synthesizing coarse single-crystal cathodes with Li-/Mn-rich or Ni-rich chemistry, which differs from the equipment- and energy-intense and long-duration mechanochemical routes that are difficult to scale up. Our approach is based on interfacial reactive wetting, mediated by transient eutectic salts in situ melted by moderate mechanical agitations, to form a colloidal suspension of nanosized oxides dispersed in liquified lithium salts. It efficiently deagglomerates the polycrystalline precursors, repacks the crystals and homogenizes the lithium-salt distribution, thus enabling facile particle coarsening later into the single-crystalline morphology with improved electrochemical performance. Single-crystalline layered oxides are much sought after as they offer high-performance promises in batteries. Here the authors report a facile and scalable planetary centrifugal mixing technique—aided by eutectic lithium salts—that enables the growth of high-quality single-crystalline cathode materials.